2021
DOI: 10.1200/jco.2021.39.15_suppl.7549
|View full text |Cite
|
Sign up to set email alerts
|

NVG-111, a novel ROR1xCD3 bispecific antibody for non-Hodgkin lymphoma.

Abstract: 7549 Background: Receptor tyrosine kinase-like Orphan Receptor 1 (ROR1) is a type I transmembrane protein is highly expressed on an array of haematological and solid tumours. NVG-111 is a humanised, tandem scFv ROR1xCD3 bispecific antibody previously shown to elicit potent killing of tumour cells in vitro and in vivo by engaging a membrane-proximal epitope in the Wnt5a-binding Frizzled domain of ROR1 and redirecting T cell activity. The in vitro potency and pharmacodynamic responses to NVG-111 were assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Patients are ≥2nd line therapy with a Bruton's tyrosine kinase inhibitor, or venetoclax (clinical trial information: 2020-000820-20). Results are pending [58].…”
Section: Novel Perspective and Bsabs In Clinical Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients are ≥2nd line therapy with a Bruton's tyrosine kinase inhibitor, or venetoclax (clinical trial information: 2020-000820-20). Results are pending [58].…”
Section: Novel Perspective and Bsabs In Clinical Developmentmentioning
confidence: 97%
“…NVG-111 is a humanized, tandem scFv bsAb binding ROR1 and CD3 and previously shown to be a potent tumor cell killer in vitro. In vivo it has also been shown to engage a ROR1 membrane-proximal epitope in the Wnt5abinding Frizzled domain and redirect T-cell activity [58]. An ongoing phase 1/2 study in patients with R/R chronic lymphocytic leukemia (CLL) and MCL is evaluating an escalated doses schedule (of 0.3 to 360 µg/day) via continuous infusion over 3 cycles (each 21 days on, 7 days off).…”
Section: Novel Perspective and Bsabs In Clinical Developmentmentioning
confidence: 99%
“…NVG-111 is a bispecific antibody that can simultaneously bind both ROR1 and CD3 molecules used to promote the activation of cytotoxic T cells through the T cell CD3 complex and selectively target the activated T cells to ROR1-positive malignant cells, with promising results in CLL and solid tumors in preclinical models. [106][107][108] CAR-T cells targeting ROR1 proved effective outcomes in patients with ROR1 pos hematological and solid malignancies. 28,98,109 The application of small-molecule TK inhibitors (TKIs), ATPcompetitive inhibitors, is one of the most effective approaches for cancer treatment targeting the catalytic domains in TKs.…”
Section: Ror1 As Target For Therapy In Cllmentioning
confidence: 99%
“…Another strategy of targeting ROR1 includes BiTEs, genetically engineered recombinant antibodies that can simultaneously bind two different epitopes or antigens. NVG‐111 is a bispecific antibody that can simultaneously bind both ROR1 and CD3 molecules used to promote the activation of cytotoxic T cells through the T cell CD3 complex and selectively target the activated T cells to ROR1‐positive malignant cells, with promising results in CLL and solid tumors in preclinical models 106–108 …”
Section: Ror1 As Target For Therapy In Cllmentioning
confidence: 99%
“…NVG-111 is the first BiAb that utilized the inherent cytotoxicity of T cells. Ongoing clinical trials of NVG-111 have shown promising results in both CLL and solid tumors, with favorable cytotoxicity[ 48 ]. Another bispecific T-cell splicer, SFG.…”
Section: Antitumor Strategies Targeting Ror1 In Gastrointestinal Cancersmentioning
confidence: 99%